The Influence of Profitability, Board of Commissioners, Independent Commissioners, and Idiosyncratic Risk on Dividend Payout Ratio - Cahyadi, Rino Tam; Purwanti, Lilik; Mardiati, Endang (Jurnal Economia, 2018)
Abstract: The Influence of Profitability, Board of Commissioners, Independent Commissioners, and Idiosyncratic Risk on Dividend Payout Ratio. This study aimed to empirically assess the influence of company’s profitability, commissioners, independent commissioners, and idiosyncratic risk on Dividend Payout Ratio (DPR). Samples were selected by using purposive sampling method and this research utilize panel data regression with common effect model to analyze the data. This study found that, profitability had a significantly positive influence on DPR, independent commissioners had a significantly negative influence on DPR; and board of commissioners and idiosyncratic risk had no influence on DPR. Keywords: profitability, board of commissioners, independent commissioners, idiosyncratic risks, dividend payout ratioAbstrak: Pengaruh Profitabilitas, Dewan Komisaris, Komisaris Independen dan Risiko Idiosinkratis Terhadap Dividend Payout Ratio. Penelitian ini bertujuan untuk menguji pengaruh langsung profitabilitas, dewan komisaris, komisaris independen, dan risiko idiosinkratis terhadap Dividend Payout Ratio (DPR). Teknik pemilihan sampel menggunakan purposive sampling dan analisis data menggunakan regresi data panel dengan model common effect. Hasil penelitian menunjukkan bahwa profitabilitas berpengaruh positif terhadap DPR, komisaris independen berpengaruh negatif terhadap DPR, sementara dewan komisaris dan risiko idiosinkratis tidak memiliki pengaruh terhadap DPR. Kata Kunci: profitabilitas, Dewan Komisaris, Komisaris Independen, risiko idiosinkratis, Dividend Payout Ratio